Crowd Powered Media Delivery: Facilitating Ubiquitous Device-To-Device File Transfers - Scott, Colin (ACM DEV 2016, 2016)
Device-to-device file transfers are pervasive in many emerging markets, but users typically only share content with close friends or informal media vendors. We seek to facilitate ubiquitous device-to-device file transfers beyond one’s immediate social network. This extended abstract outlines the research challenges we need to address and our initial plans for addressing them.